Respon Pertumbuhan dan Hasil Tanaman Edamame (Glycine max (L.) Merr.) dengan Pemberian Dosis POC Darah Sapi dan Penambahan Pupuk ZA - Pujangga (Indonesia), Affrel Adia; Astiningrum (Indonesia), Murti; Anindyawati (Indonesia), Nurul (Universitas Tidar, 2024)
This study examines the effect of doses of cattle blood liquid organic fertilizer and ZA fertilizer on the growth and yield of edamame plants (Glycine max (L.) Merr.). The study was conducted at the Soropadan Agricultural Training Center from May to August 2022. The study utilized a factorial experiment (4 x 2) arranged in a complete randomized block design with 2 factors and 3 replications. The first factor involved varying dosages of POC, with four levels: 0, 200, 400, and 600 ml per plot. The second factor was the application of ZA fertilizer at two levels: 0 kg/ha and 75 kg/ha. The results of this study showed that the application of cattle blood liquid organic fertilizer with doses of 600 ml/plot still improved the yield in parameter such as the number of filled pods per plant, weight of filled pods per plant, weight of dry seeds per plant, weight of dry seeds per m2, and weight of 100 dry seeds. The optimum result for the parameter of weight of filled pods per m2 was achieved at a dose of cattle blood liquid organic fertilizer of 434,44 ml/plot and for the parameter of protein content was achieved at a dose of 350 ml/plot. The dose of ZA fertilizer at 75 kg/ha yielded higher results for the number of filled pods per plant, weight of filled pods per plant, weight of dry seeds per plant, and weight of 100 dry seeds. The application of a dose of cattle blood liquid organic fertilizer of 352,50 ml/plot and ZA fertilizer at 75 kg/ha provided the highest yield in the number of filled pods per plant.